The coupled system of (5)1Σu+ and (5)1Πu electronic states in Rb2. (November 2017) - Havalyova, I.; Pashov, A.; Kowalczyk, P.; Szczepkowski, J.; Jastrzebski, W.
Highlights: Global deperturbation analysis. Coupled channels treatment of perturbed molecular states with spectroscopic accuracy. Modeling of quantum interference effects. Abstract: We present deperturbation analysis of the mutually perturbed (5) 1 Σ u + ← X 1 Σ g + and (5) 1 Πu  ← X 1 Σ g + band systems of Rb2 molecule, recorded under rotational resolution by polarization labelling spectroscopy technique. The L-uncoupling interaction causes large shifts of rovibrational energy levels in the low parts of both excited states, which manifest themselves in very irregular patterns of spectral lines. Besides, intensity anomalies among P ( J ) and R ( J ) lines are observed and identified as quantum mechanical interference effects. The coupled channels treatment of the (5) 1 Σ u + and (5) 1 Πu states allows to reproduce positions of majority of the observed spectral lines within the experimental uncertainty as well as to explain the unusual intensity distribution.